2021
DOI: 10.19127/mbsjohs.881342
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Child and Adolescent Psychiatry Consultations at a University Hospital and Accuracy Rates of Recognition of Childhood Psychiatric Diseases by Nonpsychiatry Specialists

Abstract: Objective: Physical and mental health are closely related. Psychiatric problems increase in the presence of a physical illness. Consultation liaison psychiatry provides a combination of medical treatment, psychiatric treatment, and psychosocial care to patients when necessary. In this study, we aimed to examine the consultation-liaison services provided by the child and adolescent psychiatry department of a university hospital within two years and to examine the accuracy rates of recognition of childhood psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 33 publications
0
5
1
Order By: Relevance
“…Furthermore, the inpatient group had a much higher proportion of girls than the outpatient group. Previous research found that the majority of child and adolescent psychiatric consults were requested for inpatients [3,[14][15][16]. In contrast, most patients consulted in this study were outpatients, with more boys as inpatients and girls as outpatients.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…Furthermore, the inpatient group had a much higher proportion of girls than the outpatient group. Previous research found that the majority of child and adolescent psychiatric consults were requested for inpatients [3,[14][15][16]. In contrast, most patients consulted in this study were outpatients, with more boys as inpatients and girls as outpatients.…”
Section: Discussioncontrasting
confidence: 64%
“…In studies conducted in our country, the most common reason for requesting consultations from child and adolescent psychiatry were suicide attempts [3,5,15,16,18]. Suicide risk assessment was the most common reason for referral to child psychiatry in a recent review [2].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…26 A study conducted in our country in 2021 shows that the most common mental disorder diagnosis is depression (19%) as a result of consultation evaluation. 27 In a one-year retrospective study, in which a total of 302 patients were included and 94% of the patients were diagnosed with mental illness, the three most common diagnoses after the first consultation evaluation were conduct disorders (30.8%), anxiety disorders (22.5%) and depressive disorders (11.3%). 28 In a study by Şimşek et al, in which they evaluated the child psychiatry consultations requested for inpatients and outpatients, the most common psychiatric diagnoses were; major depressive disorder, conduct disorder, bipolar disorder.…”
Section: Discussionmentioning
confidence: 99%